Implementation of Maqāṣid al-Sharī‘ah Principles in Islamic Financial Institutions in Supporting Sustainable Development Goals - Wahida, Wahida Rahim; Tarimana, Siti Nurul Fatimah; Rosikah; Supardin, Muhammad Ikhlas (Jurnal Al-Qadau: Peradilan dan Hukum Keluarga Islam, 2026)
Sustainable economic development has become a global agenda emphasizing the balance between economic growth, social justice, and environmental sustainability as reflected in the Sustainable Development Goals (SDGs). In this context, Islamic Financial Institutions (IFIs) possess strategic potential to support sustainable development through the implementation of maqashid al-shariah principles, which emphasize public welfare, justice, and social balance. This study aims to analyze the implementation of maqashid al-shariah principles in the practices of IFIs and their contribution to sustainable economic development. This research employed a qualitative approach with a descriptive research design. Data were collected through in-depth interviews with IFI practitioners, productive waqf managers, and Islamic finance regulators, supported by documentation studies and observations. The findings reveal that several IFIs have implemented maqashid al-shariah principles through productive sector financing, MSME empowerment, profit-sharing financing schemes, and the development of productive waqf. However, the implementation of sustainability principles still faces several challenges, including the low integration of Environmental, Social, and Governance (ESG) principles, limited innovation in green financial products, and weak institutional synergy. This study concludes that strengthening regulations, improving human resource capacity, and developing sustainable Islamic finance models are necessary for IFIs to optimally function as instruments of inclusive, equitable, and sustainable economic development.